2023
DOI: 10.3389/fspor.2023.1168731
|View full text |Cite
|
Sign up to set email alerts
|

Growing old together: What we know about the influence of diet and exercise on the aging host's gut microbiome

Abstract: The immune system is critical in defending against infection from pathogenic microorganisms. Individuals with weakened immune systems, such as the elderly, are more susceptible to infections and developing autoimmune and inflammatory diseases. The gut microbiome contains a plethora of bacteria and other microorganisms, which collectively plays a significant role in immune function and homeostasis. Gut microbiota are considered to be highly influential on host health and immune function. Therefore, dysbiosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…Age is another factor affecting the microbiome during, and after death. Aging is considered to have an impact on the intestinal microbiome ( Xu et al, 2019 ; Brooks et al, 2023 ), the diversity decreasing with age ( Leite et al, 2021 ), while, Proteobacteria being observed in higher abundances in older living subjects. During the current experiment, Firmicutes was more abundant in cases involving older adults, however, these observations are made postmortem.…”
Section: Discussionmentioning
confidence: 99%
“…Age is another factor affecting the microbiome during, and after death. Aging is considered to have an impact on the intestinal microbiome ( Xu et al, 2019 ; Brooks et al, 2023 ), the diversity decreasing with age ( Leite et al, 2021 ), while, Proteobacteria being observed in higher abundances in older living subjects. During the current experiment, Firmicutes was more abundant in cases involving older adults, however, these observations are made postmortem.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that various factors, such as diet, exercise, sex, age, or weight, can influence the diversity and richness of gut bacteria in humans [ 22 , 23 , 24 , 25 , 26 , 27 ]. Specifically, Cuesta-Zuluaga et al [ 28 ] investigated the association of age, sex, and gut bacterial alpha diversity in three large cohorts of adults.…”
Section: Discussionmentioning
confidence: 99%
“…Infants’ microbiota are predominantly made up of Lactobacilli and Bifidobacteria , which are important for immunological development and nutrition metabolism [ 22 ]. Microbial diversity rises as children grow and then levels off by early adulthood [ 23 ], though it declines again with further age [ 24 ]. Metabolic activity, and vulnerability to disease, have been linked to these changes [ 24 ].…”
Section: Normal Gut Microbiomementioning
confidence: 99%
“…Microbial diversity rises as children grow and then levels off by early adulthood [ 23 ], though it declines again with further age [ 24 ]. Metabolic activity, and vulnerability to disease, have been linked to these changes [ 24 ].…”
Section: Normal Gut Microbiomementioning
confidence: 99%